Breastfeeding: causes and consequences of early weaning (Research, Society and Development, 2020)
The objective was to analyze in the scientific evidence the factors to describe and describe the main causes and consequences of early weaning in infants, to highlight the causes and consequences of early weaning and to analyze the benefits of breastfeeding. The research is justified due to the importance of breastfeeding for infants, where early weaning is a predisposing factor for preventable diseases, such as: malnutrition, diarrhea, childhood obesity, among other public health problems, in addition to contributing to the increase infant mortality. This is a bibliographic search, where the bibliographic survey was carried out in the Scientific Electronic Lcibrary Online (SciELO), Virtual Health Library-VHL, Latin American and Caribbean Literature in Health Sciences (LILACS), Bireme and Brazilian nursing journals. The results and discussions of the study showed that the causes most described by mothers in relation to breast milk are related to a small amount and the suspicion that their milk is weak, and may present physical reasons that end up contributing to early weaning, such as some disease. It is concluded in this way that the factors that influence early weaning do not happen in isolation, but rather, caused by a series of factors.